Case report: Preputial tube-flap ureteroplasty for neoureter creation in a male dog with post ureterocolonic anastomosis complications - Yala, Wongsuda; Chumkam, Anitha; Prommarit, Ana; Sungthong, Chanakarn; Danpanang, Nut; Yippaditr, Wanchart (Frontiers in Veterinary Science, 2024)
A 16.50 kg, 5-year-old male mixed breed dog presented due to complications following a ureterocolonic anastomosis performed to manage of ureteral and urinary bladder injuries. The first revision surgery involved reimplantation of the ureters into the cranial aspect of the prepuce. Dehiscence of the anastomosed ends of the right ureter was observed postoperatively. A second revision surgery was then performed, involving a preputial tube-flap ureteroplasty via preputiotomy. A longitudinal flap was raised from the prepuce and anastomosed to the end of the right ureter to create a neoureter and reduce tension at the anastomosis site. Postoperative follow-up evaluations at 10 days and 6 months revealed no unexpected complications. Six months follow-up, the owner reported that the dog exhibited a satisfactory quality of life.